PENGEMBANGAN INSTRUMEN SUBJEKTIF DAN OBJEKTIF PEMBELAJARAN TEKS CERPEN SISWA SMA KELAS XI - Anggraini S, Dwi; Hilal, Iqbal; Ariyani, Farida (FKIP Universitas Lampung, 2020)
This study aims to produce a learning evaluation instrument product that is both subjective and objective test scripts based on HOTS (Higher Order Thinking Skills). The test instrument in this study can be used to measure the level of success of students in achieving learning objectives on indicators describing life. This research uses the Research and Development method. The results of this research and development are test instruments in the form of multiple choice questions totaling 30, description questions totaling 10, and matchmaking questions totaling 10 which have been declared fit for use by material experts and linguists. The results of the validation of the material experts obtained a mean score of 4.4 and an average percentage of 88%. The results of the validation of linguists obtained an average score of 4.3% and an average percentage of 87%, so that the subjective and objective test instruments in this study were suitable for teaching and learning activities. Penelitian ini bertujuan untuk menghasilkan produk instrumen evaluasi pembelajaran yaitu naskah tes baik subjektif maupun objektif berbasis HOTS (Higher Order Thinking Skills). Instrumen tes dalam penelitian ini dapat digunakan untuk mengukur tingkat keberhasilan siswa dalam mencapai tujuan pembelajaran pada indikator menjelaskan nilai-nilai kehidupan. Penelitian ini menggunakan metode Research and Development. Hasil penelitian dan pengembangan ini adalah instrumen tes berbentuk soal pilihan ganda berjumlah 30, soal uraian berjumlah 10, dan soal menjodohkan berjumlah 10 yang telah dinyatakan layak digunakan oleh ahli materi dan ahli bahasa. Hasil validasi ahli materi diperoleh rerata skor 4,4 dan rerata persentase 88%. Hasil validasi ahli bahasa diperoleh rerata skor 4,3% dan rerata persentase 87%, sehingga instrumen tes subjektif dan objektif dalam penelitian ini laik digunakan untuk kegiatan belajar mengajar. Keywords: Development, Assessment, Short story text